Clear fluid detector using Optical technique - Siti Nasuha Zainal Abidin (Universiti Malaysia Perlis, 2008)
Nowadays, the optical technologies are very young in Malaysia. This technology still in the research to changes the sensor technologies. The detector requirement are very similar to those of optoelectronic sources; that is, should have high sensitivity at operating wavelength, high fidelity, fast response, low noise and low cost .This project is build by using the optical technique to detect the clearness of liquid which have two circuit include the transmitter and receiver. This application relates to novel detector for sensing the presence and refractive index of a fluid. At this project also design to find the differ between the absences and presences of liquid with the different voltage which measure in the detector circuit and analyzer and method for measuring the properties of a liquid sample when through an opaque housing. This project designs especially to liquid in a tube or similar restricted vessel which has a wall that will transmit light. It also to provide the detector circuit having a light source and photo detector package which is low in cost to fabricate and which is stable in operation over a wide temperature range.